HUBUNGAN PENGETAHUAN PERAWAT DENGAN PENERAPAN PATIENT SAFETY - Tenri Diah T.A (Jurnal Ilmiah Kesehatan Media Husada, 2023)
Nurses' knowledge about patient safety is very important because nurses must show a positive attitude in supporting patient safety programs so that they carry out nursing practices safely. Patient Safety is a top priority in health services and is the first step to improve service quality and is related to hospital quality and image. In Indonesia alone, new incident reports were recorded at the Hospital Patient Safety Committee (KKPRS) of incidents from September 2013 to August 2014 as many as 145 incidents due to medical error cases. RSUD Haji Makassar has one of the programs in infection prevention and control related to health services but it has not been fully realized. This study aims to determine the relationship between the level of knowledge of nurses in the class 3 treatment room at the Haji Makassar Hospital with efforts to implement patient safety. The type of research used is cross sectional using a descriptive approach. Based on the results of the analysis, there is a relationship between the level of knowledge and the application of patient safety with a p-value of 0.006 <0.05. It is recommended to the hospital to organize education, training, and socialization to all health workers regarding efforts to implement patient safety, especially to nurses in order to increase nurses' knowledge regarding the application of patient safety